Influence of harvest mechanization in economic and financial viability of coffee farming in Southern Minas Gerais - Lanna, Giovani Blasi Martino; Reis, Ricardo Pereira (Coffee Science - ISSN 1984-3909, 2012)
This study was conducted with the aim of evaluating the influence of mechanization on economic and financial feasibilityof establishing coffee plantations in the southern region of the State of Minas Gerais. Thus, techniques or project analysis indicatorswere used to verify the economic and financial feasibility of investing in coffee activity. The main results conclude that, the use ofmechanization in the coffee harvest, when possible, has a significant impact on the composition of costs, which directly influences theperformance of the coffee enterprise in the southern region of Minas Gerais. Finally, we note that the price of coffee has an influenceon the economic viability of coffee investment which is essential to the profitability. Thus, the rural entrepreneur must use a managementstyle that emphasizes planning and cost management and seeks to optimize the productive resources used in coffee plantations, whilealso using market mechanisms to minimize the risk of coffee price variability in the future market.